Evidence for induction of DNA double strand breaks in the bystander response to targeted soft X-rays in CHO cells. - Kashino, G; Prise, K; Schettino, G; Folkard, M; Vojnovic, B; Michael, B; Suzuki, K; Kodama, S; Watanabe, M (2004)
This study investigated the role of DNA double strand breaks and DNA base damage in radiation-induced bystander responses in Chinese hamster ovary (CHO) cell lines. Two CHO repair-deficient clones, xrs5 (DNA double strand break repair-deficient) and EM9 (DNA base excision repair-deficient) were used in addition to the wild type (CHO). The Gray Cancer Institute ultrasoft X-ray microprobe is a powerful tool for investigating the bystander response, because it permits the irradiation of only a single nucleus of a cell, as reported previously. In order to investigate the bystander effect in each repair-deficient cell line, we irradiated a single cell within a population and scored the formation of micronuclei. When a single nucleus in the population was targeted with 1 Gy, elevated numbers of micronuclei were induced in the neighbouring unirradiated cells in the EM9 and xrs5 cell lines, whereas induction was not observed in CHO. The induction of micronuclei in xrs5 was significantly higher than that in EM9. Under these conditions, the surviving fraction in the neighbouring cells was significantly lower in xrs5 than in the other cell lines, showing a higher cell killing effect in xrs5. To confirm that bystander factors secreted from irradiated cells caused these effects, we carried out medium transfer experiments using conventional X-irradiation. Medium conditioned for 24 h with irradiated cells was transferred to unirradiated cells and elevated induction of micronuclei was observed in xrs5. These results suggest that DNA double strand breaks rather than base damage are caused by factors secreted in the medium from irradiated cells.